STUDY ON THE EFFECT OF SURFACE COMPOSITE STRENGTHENING ON THE SURFACE INTEGRITY OF 18CrNiMo7⁃6 CARBURIZED GEAR STEEL - WANG Zhen; SUN Hao; CUI YiLong; LI LinYan; WANG Tao; HAN JiaoBao (Jixie qiangdu, 2024)
Shot peening process is widely used in the manufacturing process of gears and other basic components， and its own limitations limit the enhancement of the surface integrity of the workpiece. In order to further improve the surface integrity of the workplece， A combination of numerical simulation and experimental methods was utilized to study the effect of two surface composite strengthening processes， such as double shot peening and shot peening-ultrasonic rolling， on the surface integrity of 18CrNiMo7-6 carburization gear steel samples， and mainly analyzed the effect of the two composite strengthening processes on the improvement of surface integrity of the shot peened samples. The results show that the maximum value of the residual compressive stress of the double shot peening sample is 1 359.56 MPa， locates at the depth of 0.08 mm， and the maximum value of the residual compressive stress of the shot peening-ultrasonic rolling peening sample is 1 329.05 MPa， locates at the depth of 0.25 mm. Compare with the single shot peening sample， the surface roughness of the double shot peening sample and the shot peening-ultrasonic rolling sample is 29.42% and 29.42% lower than that of the single shot peening sample. Compare with the single shot peening samples， the surface roughness of the double shot peening samples and shot peening-ultrasonic tumbling peening samples decreases by 29.42% and 62.76%， respectively， the surface microhardness increases by 8.70% and 17.60%， and the standard deviation of the surface node compressive residual stress value decreases by 23.36% and 89.50%. The shot peening-ultrasonic rolling process is more effective in enhancing the surface hardness， thickness of the residual stress layer and uniformity of the residual compressive stress， as well as reducing the surface roughness of the specimens， and can effectively improve the surface integrity of the shot peened samples.